Kepemimpinan Perempuan Sebagai Katalis Transformasi Sosial di Kampung Buruh Migran - Cahyawati, Unik Dian (Pusat Studi Wanita dan Keluarga UGM, 2025)
Migrant workers face various forms of vulnerability, including human trafficking, fraud, physical and sexual violence, and administrative issues that impact their families. Unfortunately, many of these issues have not received adequate formal attention, making grassroots initiatives highly essential. One prominent figure in migrant worker advocacy is Maizidah Salas, a former survivor who now actively advocates for migrant workers' rights through Kampung Buruh Migran in Kaliwiro, Wonosobo. This study employs a case study method, utilizing intersectionality theory and transformational leadership theory to analyze how Maizidah Salas' identity as a woman, former migrant worker, and activist contributes to the social movement. The findings indicate that her experiences and leadership position her as a catalyst in strengthening migrant worker solidarity, raising awareness of their rights, helping to manage migrant workers' families in their home villages and promoting more inclusive policy changes. This study affirms that grassroots women's leadership plays a strategic role in social transformation, particularly in advocating for justice and protection for migrant workers.